Let-7 microRNA-dependent control of leukotriene signaling regulates the transition of hematopoietic niche in mice - Xuan Jiang (Nature Portfolio, 2017)
Hematopoietic stem and progenitor cells are generated first from the vascular endothelium of the dorsal aorta and then the fetal liver but what regulates this switch is unknown. Here, the authors show that changing miRNA biogenesis and leukotriene B4 signaling in mice modulates this switch in the niche.